2014
DOI: 10.18632/oncotarget.2200
|View full text |Cite
|
Sign up to set email alerts
|

HERG1 functions as an oncogene in pancreatic cancer and is downregulated by miR-96

Abstract: Pancreatic cancer is an aggressive malignancy with an extremely poor prognosis. The human ether-a-go-go-related potassium channel (HERG1) is a human rapid delayed rectifier, which is involved in many crucial cellular events. In this article, we find that HERG1 expression is dramatically increased both in pancreatic cancer tissues and cell lines, and that increased HERG1 expression is significantly related to the development of pancreatic cancer. HERG1 silencing in pancreatic cancer-derived cell lines PANC-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 47 publications
(45 reference statements)
3
59
0
1
Order By: Relevance
“…Notably, the inhibitory effect of miR-96 on pancreatic cancer cell proliferation has been clearly elucidated in the past few years [20, 51, 89, 90]. In pancreatic cancer, three important oncogenes, including KRAS [51], human either a go-go-related gene type 1 (HERG1) [89] and Glypican 1 (GPC1) [90], are known to be miR-96 target genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the inhibitory effect of miR-96 on pancreatic cancer cell proliferation has been clearly elucidated in the past few years [20, 51, 89, 90]. In pancreatic cancer, three important oncogenes, including KRAS [51], human either a go-go-related gene type 1 (HERG1) [89] and Glypican 1 (GPC1) [90], are known to be miR-96 target genes.…”
Section: Resultsmentioning
confidence: 99%
“…In pancreatic cancer, three important oncogenes, including KRAS [51], human either a go-go-related gene type 1 (HERG1) [89] and Glypican 1 (GPC1) [90], are known to be miR-96 target genes. KRAS, aberrantly activated in approximately 90% of pancreatic cancers [91], can promote abnormal cell proliferation by activating PI3K/Akt, NF-κB and ERK signaling pathways [9295].…”
Section: Resultsmentioning
confidence: 99%
“…miR-96 functions as an oncomiR by promoting cellular growth, invasiveness and metastasis in breast cancer [104] , pancreatic cancer [105] and HCC [106] . miR-96 directly targets AKT1S1 that encodes for PRAS40, a negative regulator of mTOR kinase, which prevents the binding of mTOR to its substrates [107] .…”
Section: Mirnas That Activate Mtor Pathwaymentioning
confidence: 99%
“…The results of the current study revealed that HERG1 expression was significantly increased in bladder cancer cell lines compared with that in SV-HUC-1 cells. Bioinformatic analysis has demonstrated that HERG1 may be a target gene of miR-96 (39). The present study also utilized a dual luciferase reporter assay to verify that HERG1 was a target gene of miR-96.…”
Section: Cell Cycle % Apoptosis % ---------------------------------mentioning
confidence: 81%